Proteomic signatures of human oral epithelial cells in HIV-infected subjects. - Elizabeth Yohannes; Santosh K Ghosh; Bin Jiang; Thomas S McCormick; Aaron Weinberg; Edward Hill; Faddy Faddoul; Mark R Chance (PLoS ONE)
The oral epithelium, the most abundant structural tissue lining the oral mucosa, is an important line of defense against infectious microorganisms. HIV infected subjects on highly active antiretroviral therapy (HAART) are susceptible to comorbid viral, bacterial and fungal infections in the oral cavity. To provide an assessment of the molecular alterations of oral epithelia potentially associated with susceptibility to comorbid infections in such subjects, we performed various proteomic studies on over twenty HIV infected and healthy subjects. In a discovery phase two Dimensional Difference Gel Electrophoresis (2-D DIGE) analyses of human oral gingival epithelial cell (HOEC) lysates were carried out; this identified 61 differentially expressed proteins between HIV-infected on HAART subjects and healthy controls. Down regulated proteins in HIV-infected subjects include proteins associated with maintenance of protein folding and pro- and anti-inflammatory responses (e.g., heat-shock proteins, Cryab, Calr, IL-1RA, and Galectin-3-binding protein) as well as proteins involved in redox homeostasis and detoxification (e.g., Gstp1, Prdx1, and Ero1). Up regulated proteins include: protein disulfide isomerases, proteins whose expression is negatively regulated by Hsp90 (e.g., Ndrg1), and proteins that maintain cellular integrity (e.g., Vimentin). In a verification phase, proteins identified in the protein profiling experiments and those inferred from Ingenuity Pathway Analysis were analyzed using Western blotting analysis on separate HOEC lysate samples, confirming many of the discovery findings. Additionally in HIV-infected patient samples Heat Shock Factor 1 is down regulated, which explains the reduced heat shock responses, while activation of the MAPK signal transduction cascade is observed. Overall, HAART therapy provides an incomplete immune recovery of the oral epithelial cells of the oral cavity for HIV-infected subjects, and the toxic side effects of HAART and/or HIV chronicity silence expression of multiple proteins that in healthy subjects function to provide robust innate immune responses and combat cellular stress.